IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT THROUGH COLLABORATIVE STRATEGIC READING (CSR - Seto Sudarmo; Gatot Soetapa; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research was conducted to the eighth grade students of Madrasah Tsanawiah Negeri 1 Pontianak in academic year 2016/2017. The aim of this research was to find out how well the use of Collaborative Strategic Reading in improving students’ reading comprehension. The problem includes the difficulties in comprehending the narrative text and finding the elements of narrative text. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. The researcher observed the improvement of students’ reading comprehension by collecting the data through observation and measurement technique. The tools of data collecting were observation checklist, field note, and test. This research was implemented to 42 eighth grade students of Madrasah Tsanawiah Negeri 1 Pontianak in academic year 2016/2017. The finding of this research shows that there was an improvement on students’ reading comprehension through collaborative strategic reading. Four steps on Collaborative strategic reading helped the students in comprehending text. The four steps are previewing, click n clunk, get the gist and wrap up. The steps of collaborative reading help the students to improve their skill in comprehending the theme, supporting details, vocabulary, reference, and inference on narrative text. The quality of teaching improved the reading comprehension. The reading skill improvement by applying collaborative strategic reading could be seen from students’ activity through collaborative strategic reading stages and students’ test score. The researcher stopped on cycle 3 and decided the improvement of the reading comprehension is done.Keywords: Improving, Reading, Collaborative Strategic Reading, Narrative Text